2015
DOI: 10.1007/s00701-015-2544-z
|View full text |Cite
|
Sign up to set email alerts
|

A basic model for training of microscopic and endoscopic transsphenoidal pituitary surgery: the Egghead

Abstract: Our model, the Egghead, is affordable, offers tactile feedback and allows infinite repetitions in basic training for pituitary surgery. It can be used for training of advanced neurosurgical residents, who thus far have very few possibilities of acquiring endoscopic experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Comparisons between the two endoscopes (Table I) found no evidence of significant differences between the time (P = .153) or the adjustment time (P = .067), although the trend was for the latter to be longer in the 3D endoscopes irrespective of whether using this endoscope first or second. However, past pointing was found to be significantly lower when using 3D endoscopes (median 0 vs. 2, P = .025), and depth perception (8 vs. 4, P < .001) Adjustment Time (seconds) 9 (5-13) 10 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) .067…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons between the two endoscopes (Table I) found no evidence of significant differences between the time (P = .153) or the adjustment time (P = .067), although the trend was for the latter to be longer in the 3D endoscopes irrespective of whether using this endoscope first or second. However, past pointing was found to be significantly lower when using 3D endoscopes (median 0 vs. 2, P = .025), and depth perception (8 vs. 4, P < .001) Adjustment Time (seconds) 9 (5-13) 10 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) .067…”
Section: Resultsmentioning
confidence: 99%
“…Other specialities, however, including neurosurgery and ophthalmology, as well as junior doctors with little to no endoscopic experience, are required to acquire a new skill set using an unfamiliar tool while operating in delicate surgical fields. 8,9 In 2012, a new 4-mm three-dimensional (3D) endoscope was introduced primarily to overcome the lack of stereopsis. 3D endoscopes have encountered an evolution of their own through improvements in image clarity and endoscopic quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadaveric models represent invaluable training aids; however, merely manipulating orbital fat and anatomy identification does not adequately prepare the surgeon for the technical challenges of dissecting orbital pathology away from sensitive neurovascular structures within the intraconal space. Although numerous training models in endoscopic skull base surgery have been described, [20][21][22] to date no known orbital models have been reported that successfully simulate orbital pathology.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The use of 3-dimensional models has improved training feasibility; however, these models lack the intricacies of complex human anatomy, especially in relation to vascular injury. 24 Anesthesia models have been developed to control hypotension during simulated training experiences, 25 but until recently, simulated vascular complication models for surgical training have not been readily available. The live sheep model is the most comprehensive model addressing vascular injury repair, but it is difficult to replicate at most training programs and is limited in that human anatomy cannot be fully appreciated.…”
Section: Introductionmentioning
confidence: 99%